Productivity losses and treatment cost of benign prostatic hyperplasia in Ghana - Daniel Senanu Dadee-Seshie; Sedem Godson Agbeteti; Banabas Kpankyaano; Aishah Fadila Adamu; Selase Kofi Adanu; Yakubu Alhassan; Maxwell Ayindenaba Dalaba; Kekeli Kodjo Adanu (PLoS ONE, 2026)
Benign Prostatic Hyperplasia (BPH) is a common condition among ageing men, characterized by lower urinary tract symptoms that significantly impact the quality of life and economic productivity of affected individuals. The financial burden of BPH extends beyond direct medical expenses to include direct non-medical costs and productivity losses. In Ghana, limited data exist on the cost implications of BPH, leaving a critical gap in healthcare planning and resource allocation. We aimed to determine the cost and productivity losses associated with diagnosing and managing BPH at the Ho Teaching Hospital. A cross-sectional cost-of-illness study was conducted at the Urology Unit of the Ho Teaching Hospital. Data was collected from 105 patients diagnosed with BPH using structured questionnaires from 11 th June 2024–30 th September 2024. Direct monthly medical costs, including consultation, diagnostics, medication, and surgical interventions, were calculated using a bottom-up approach. Direct monthly non-medical costs covered transportation, food, lodging, and caregiver expenses, while productivity losses were estimated based on absenteeism and reduced working hours, using the human capital approach. The mean monthly direct medical cost per patient was GHS 890.11 (USD 60.35), with surgeries accounting for 30% of total expenses. The total direct non-medical costs, dominated by transportation (66.3%), amounted to GHS 9,842.00 (USD 667.25). Productivity losses due to absenteeism and caregiving responsibilities totalled GHS 4,746.28 (USD 321.78), with 30% of employed patients missing work. Notably, direct medical costs contributed the highest economic burden (86.5%), surpassing direct non-medical costs (9.1%) and productivity losses (4.4%). BPH imposes a significant financial burden on patients and households in Ghana, driven by high out-of-pocket medical costs, non-medical expenses, and lost productivity. The findings underscore the need for cost-effective treatment strategies, improved health insurance coverage, and targeted interventions to alleviate financial hardships associated with BPH management.